2015
DOI: 10.1183/13993003.00622-2015
|View full text |Cite
|
Sign up to set email alerts
|

Progressive ventilation inhomogeneity in infants with cystic fibrosis after pulmonary infection

Abstract: Measures of ventilation distribution are promising for monitoring early lung disease in cystic fibrosis (CF). This study describes the cross-sectional and longitudinal impacts of pulmonary inflammation and infection on ventilation homogeneity in infants with CF.Infants diagnosed with CF underwent multiple breath washout (MBW) testing and bronchoalveolar lavage at three time points during the first 2 years of life.Measures were obtained for 108 infants on 156 occasions. Infants with a significant pulmonary infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 60 publications
3
37
0
1
Order By: Relevance
“…We found no associations between the presence of any other individual pathogens and FOT outcomes. A previous study by the AREST CF group showed that the presence of H. influenzae in the first 2 years of life was associated with persistently lower forced expiratory volume in 0.75 s and forced vital capacity up to school age [40] and increased LCI in infancy [41]. In addition, BRUMBACK et al [42] found that recent H. influenzae infection was associated with lower forced vital capacity in preschool children with CF.…”
Section: Discussionmentioning
confidence: 99%
“…We found no associations between the presence of any other individual pathogens and FOT outcomes. A previous study by the AREST CF group showed that the presence of H. influenzae in the first 2 years of life was associated with persistently lower forced expiratory volume in 0.75 s and forced vital capacity up to school age [40] and increased LCI in infancy [41]. In addition, BRUMBACK et al [42] found that recent H. influenzae infection was associated with lower forced vital capacity in preschool children with CF.…”
Section: Discussionmentioning
confidence: 99%
“…During last decades, an increased interest for MBW method among patients suffering from CF has been noted [3,4,[33][34][58][59][60][61][62][63] MBW is a non-invasive method, feasible to be performed and without the risk of radiation exposure [64]. A lot of studies have suggested that LCI has the advantage over FEV 1 to detect CF lung disease in earlier stages [21,36,38,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ability of spirometry to identify abnormal lung function in infants and young children with CF, the LCFC showed that LCI measured by MBW was more sensitive than spirometry for the detection of structural lung disease. AREST CF data show that infants who had a prior infection had a progressive increase in ventilation inhomogeneity compared to infants who were never infected [25]. While increased LCI was associated with infections, it was insensitive to detect structural abnormalities in infants [26].…”
Section: Lung Functionmentioning
confidence: 99%